Nurse Staffing Levels and Patient-Reported Missed Nursing Care. Issue 4 (October 2015) - Dabney, Beverly Waller; Kalisch, Beatrice J.
Abstract : A total of 729 inpatients were surveyed using the MISSCARE Survey–Patient . Missed timeliness, patient reports of the time it took for them to receive care from nursing staff, was negatively associated with total nursing staff hours of care per patient-day ( r = −0.09, P = .015), registered nurse (RN) hours per patient-day ( r = −0.14, P = .0002), and RN skill mix ( r = −0.13, P = .0004). RN skill mix was also a predictor of missed timeliness ( P = .01). Abstract : Supplemental Digital Content is Available in the Text.